Transformative printing: communication in visual arts of awareness for educating Malaysia's street children - Ab Aziz, Nurul Izza; Mokhtar, Mumtaz; Mohamed Shaari, Zuriati; Abdul Rahim, Rosliza; Ismail, Irma Murni (College of Creative Arts, 2025)
This studio-based research examines the use of visual communication arts to highlight the exclusion of street children in Malaysia from formal education due to the absence of essential identification documents. While government agencies such as SUHAKAM play an important role, non-governmental organizations (NGOs) have become key advocates in improving educational access. The study focuses on two NGOs, Yayasan Chow Kit and SUKA Society, both of which provide educational opportunities for marginalized and undocumented children. The project adopts a structured fourstep studio methodology based on Wallas (2014), comprising: (i) Theme, (ii) Concept, (iii) Screen, and (iv) Print. Art Trivium students from UiTM Shah Alam applied this framework to produce screen-printed designs on functional items and translating complex social issues into visually accessible narratives. The findings indicate that this methodological approach effectively enhanced students’ critical awareness and ability to communicate social issues through visual means. The resulting artworks demonstrated the potential of visual communication as a tool for advocacy fostering empathy and public discourse on educational inequality. Overall, the study confirms that visual communication transcends aesthetic expression to function as a medium for social engagement. The initiative aligns with Sustainable Development Goals (SDGs) 4: Quality Education, 5: Gender Equality and 10: Reduced Inequalities, highlighting the role of visual arts in promoting inclusivity, equity and social resilience.